Differences in the knowledge and compliance with secondary prevention of stroke between transient ischaemic attack patients with and without subsequent stroke. Issue 19 (21st January 2014) - Zhao, Jingjing; Zhou, Muke; Guo, Jian; Zhang, Jingjing; Yang, Yaqiong; Yu, Fan; He, Li
<x xml:space="preserve">Abstract</x> Aims and objectives To evaluate the differences in the knowledge and compliance with secondary prevention of stroke between transient ischaemic attack patients with and without subsequent stroke. Background No previous study has demonstrated whether there are differences in the knowledge and compliance with secondary prevention of stroke between transient ischaemic attack patients with and without subsequent stroke. If there are differences, the health education regarding the stroke knowledge should be conducted separately and differently for the two groups. Methods and design We consecutively recruited 355 transient ischaemic attack patients with/without subsequent stroke from our hospital from 1 December 2008–31 December 2011. There were 304 patients receiving health education both upon hospital discharge and 90 days after discharge. Through telephone interviews, six months after discharge, only 180 patients completed the survey to determine in detail their general knowledge and compliance with secondary prevention of stroke. Results The transient ischaemic attack patients with subsequent stroke exhibited a higher identification rate of speech disorder, weakness and decreased sensation or inability to feel things, compared with those without subsequent stroke (76·1 vs. 66·3%, p < 0·05; 91·5 vs. 73·5%, p < 0·05; 62·2 vs. 46·9%, p < 0·05). The compliance rates to antiplatelet agents and statins therapy were higher in transient ischaemic attack patients with subsequent stroke compared with those without subsequent stroke (80·5 vs. 65·3%, p < 0·05; 53·7 vs. 35·7%, p < 0·05). Conclusions The transient ischaemic attack patients with subsequent stroke exhibit a higher identification rate of most of the warning signs of stroke and a better compliance with antiplatelet agents and statins therapy of stroke compared with those without subsequent stroke. Thus, we suggest that transient ischaemic attack patients should receive additional health education to increase their awareness of the harms of stroke. Relevance to clinical practice Clinicians should be aware of conducting different health education to patients with transient ischaemic attack and stroke. Also, it is important to give health education to individualised patients based on their actual risk of stroke.